Failed catharsis after the Second World War - Bijelić Biljana (Temida)
The Second World War is not relevant only in historical and political context. Its unsolved character is usually mentioned as one of the causes of the 1990 war. The after war policy of identity is especially relevant for today’s difficulties in consideration of collective responsibility and achieving reconciliation between communities which were in conflict. Croatian example of war crimes against Serbs in the Second World War is especially illustrative. However, that is only one of many Yugoslavs’ examples, where ethnic violence in after war period was overshadowed by general suffering from foreign occupants and local traitors in the Second World War. Instead of reassessment of existing ethnic and national identities, the process of reconciliation between Croatian and Serbian community after the Second World War was exhilarated with radical changes of collective identities.